2008
DOI: 10.1001/jama.300.10.1135
|View full text |Cite
|
Sign up to set email alerts
|

Student Body Racial and Ethnic Composition and Diversity-Related Outcomes in US Medical Schools

Abstract: Context Many medical schools assert that a racially and ethnically diverse student body is an important element in educating physicians to meet the needs of a diverse society. However, there is limited evidence addressing the educational effects of student body racial diversity. Objective To determine whether student body racial and ethnic diversity is associated with diversity-related outcomes among US medical students. Design, Setting, and Participants A Web-based survey (Graduation Questionnaire) administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
239
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(240 citation statements)
references
References 19 publications
0
239
0
1
Order By: Relevance
“…In addition, underrepresented minority students, regardless of campus diversity, were more likely to plan to practice in underserved areas. 37 Numerous studies have confirmed this trend of students practicing in underserved areas, thus improving access to care. 3 Moreover, ethnic and linguistic concordance has consistently been associated with increased patient satisfaction and self-reported quality of care.…”
Section: Diversity and Health Care Disparitiesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, underrepresented minority students, regardless of campus diversity, were more likely to plan to practice in underserved areas. 37 Numerous studies have confirmed this trend of students practicing in underserved areas, thus improving access to care. 3 Moreover, ethnic and linguistic concordance has consistently been associated with increased patient satisfaction and self-reported quality of care.…”
Section: Diversity and Health Care Disparitiesmentioning
confidence: 92%
“…20,30,[34][35][36] Student body racial and ethnic diversity has had a positive impact on student attitudes about the value of diversity, cultural competence, and improved access to care for underserved patients. [37][38][39] Students at diverse medical colleges/schools had significantly higher concordance scores related to preparedness to care for underrepresented minorities and endorsement of equal access to healthcare, compared to colleges/schools with a less diverse student body. In addition, underrepresented minority students, regardless of campus diversity, were more likely to plan to practice in underserved areas.…”
Section: Diversity and Health Care Disparitiesmentioning
confidence: 96%
“…The definition of curriculum also considers who is trained, acknowledging the importance of student diversity, [14][15][16] particularly in improving quality of education, preparing students to serve diverse populations [17][18][19] and extending healthcare delivery to underserved communities. 20 UCT has long recognised that admission of students from a politically segregated and deliberately under-resourced schooling system would create challenges for students and teachers, 21 and sought to avoid the mistakes of unsupported access resulting in high dropout rates experienced in SA higher education.…”
Section: Student Access and Equitymentioning
confidence: 99%
“…see Lievens, Ones, & Dilchert, 2009). Furthermore, legitimate educational and healthcare benefits can derive from the student and professional body reflecting the population from which it is drawn (Komaromy, Grumbach, & Drake, 1996;Lakhan, 2003;Saha, Guiton, Wimmers, & Wilkerson, 2008;Tiffin, Dowell, & McLachlan, 2012;Whitla et al, 2003). There are, therefore, various reasons why it is imperative that selection for medical school is especially thorough and fair.…”
Section: Introductionmentioning
confidence: 99%